Pengaruh Penerapan Model Pembelajaran Problem Solving Terhadap Peningkatan Kemampuan Berpikir Kritis Matematis pada Siswa SMK - Ima Halimatusa'diah; Reviandari Widyatiningtyas; Irmawan (EDUCARE, 2014)
This research is motivated by mathematical thinking ability of students is still low, therefore carried out a study on the application of learning models in learning Mathematics Problem Solving. The purpose of this study was to find out: (1) whether there was an increase in students 'critical thinking skills in learning with the Problem Solving model (2) whether the improvement of students' mathematical critical thinking skills in learning with Problem Solving learning models was better than students learning by methods expository, quality improvement of students' critical thinking skills after using the Problem Solving learning model. The method used in this study is a quasi-experimental method. The research instrument used in this study was a written test of students' mathematical critical thinking skills and non-test instruments, namely the observation sheet. The results of the study showed that (1) there was an increase in students' critical thinking skills in learning with Problem Solving learning models (2) an increase in mathematical critical thinking skills of students learning with the Problem Solving model was better than students who learned using the expository method.